Assessment of operatorsâ response time on safe operation of distillation columns: A process dynamic analysis - Mukharror, D.A. (Institution of Chemical Engineers, 2021)
Dynamic simulation has been instrumental in delivering solutions to ensure safety and controllability of process plants. In this work, dynamic simulations were performed as a follow up of a Layer Of Protection Analysis (LOPA) study for two existing distillation columns. Cooling water and reflux failures were considered as the event scenarios. Models were developed and run in iCON-Symmetry v2020.3 environment, considering all related data taken from as built documents. In Column C-1, cooling water failure event leads to the high-high pressure alarm at about 7 min, followed by opening of its five PSVs simultaneously at about 2 min afterwards. Liquid level in the reflux drum drops quickly due to its flow control setup and the reflux pump is shut off about 5 min afterwards. Reflux failure case for this Column C-1 only increases the pressure by about 0.4 bar and hence, all PSVs remain close. This is mainly attributed to the huge capacity of the condenser and the volume of the column itself. In Column C-2, the high-high pressure alarm alerts the operator after at about 3-4 min, while its three PSVs open within about 1-2 min afterwards. Its more rapid overpressure situation is caused by the reduced reflux flowrate (level-controlled) as well as the presence of vapor fraction in the feed. The reflux pump is shut off at about 9 min after the PSVs open. Its reflux failure case is less severe compared to its cooling water failure. Nonetheless, the pressure does increases significantly and the PSVs open at about 9-10 minutes. Overall, it is shown that all PSVs have been sized adequately to cater for the cooling water failure as the worst-case scenario, as recorded in the document of relief load calculations. In addition to this, even though operators on the field do not have sufficient time to react, operators in the control room, however, can quickly push the safety switch on the control board to isolate the columns. Thus, the operating procedure is updated accordingly so that the operator has to push the switches within two and one minutes after the alert of high-high pressure alarms for Column C-1 and C-2, respectively. Â© 2021 IChemE